2013
DOI: 10.3803/enm.2013.28.1.33
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Body Composition and Coronary Artery Calcification in Apparently Healthy Korean Adults

Abstract: BackgroundWe investigated the association of coronary artery calcium score (CACS) with body composition and insulin resistance in apparently healthy Korean adults.MethodsNine hundred forty-five participants (mean age, 48.9 years; 628 men) in a medical check-up program were selected for analysis. Body composition was assessed by bioelectrical impedance analysis (BIA). Insulin resistance was evaluated using the homeostasis model assessment of insulin resistance (HOMA-IR). The CACS was assessed by multidetector c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 19 publications
1
24
1
1
Order By: Relevance
“…In a study performed in 321 Japanese participants, Ohashi et al [24] reported that visceral adiposity was significantly associated with the presence and extent of CAC. In a study of 924 healthy Koreans, CAC showed a significant positive correlation with WC, WHR, and WHR as the most significant predictors for CAC [7]. Our study showed that the group that met the criteria for obesity by both BMI and WC had the highest CAC risk, followed by the group that met the criteria for overweight by BMI and obesity by WC.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In a study performed in 321 Japanese participants, Ohashi et al [24] reported that visceral adiposity was significantly associated with the presence and extent of CAC. In a study of 924 healthy Koreans, CAC showed a significant positive correlation with WC, WHR, and WHR as the most significant predictors for CAC [7]. Our study showed that the group that met the criteria for obesity by both BMI and WC had the highest CAC risk, followed by the group that met the criteria for overweight by BMI and obesity by WC.…”
Section: Discussionmentioning
confidence: 52%
“…Thus, indices that reflect central obesity such as WC, waist-hip ratio (WHR), and waist-height ratio (WHtR) have gained popularity for the measurement of relative visceral fat distribution [56]. Visceral obesity is a strong risk factor for metabolic disorders and is associated with increased risk for CVD [47]. …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, not the actual amount of adipose tissue, but where they are deposited affects more of their metabolic function; for example, visceral fat is the starting point for the insulin resistance and atherosclerosis as it is more prone to lipolysis and releases free fatty acid to the circulation, whereas subcutaneous fat is known for the protective effect against insulin resistance and obesity [2], [3].…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Increased coronary artery calcium score (CACS) is known to correlate with the risk of cardiovascular disease and various metabolic diseases. 18,19 A recent study reported the association of increased CACS with development of ischemic stroke in a large CAC-based cohort. 20 There is no single imaging method for the determination of whole-body atherosclerotic status.…”
mentioning
confidence: 99%